Gaming disorder and internet addiction: A systematic review of resting-state EEG studies. (August 2020) - Burleigh, Tyrone L.; Griffiths, Mark D.; Sumich, Alex; Wang, Grace Y.; Kuss, Daria J.
Highlights: Gaming disorder patients experience raised delta and theta activity and reduced beta activity. Gaming disorder coherence analysis suggest altered brain activity in the mid-to-high frequency range. Internet addiction patients experience raised gamma and reduced beta and delta activity. Results suggest that gaming disorder and internet addiction are unique neurophysiological constructs. Abstract: Neurophysiological studies of Gaming Disorder (GD) and internet addiction (IA) are providing important insight into neurocognitive mechanisms underpinning these disorders, which will enable more accurate diagnostic classification. Electroencephalography (EEG) has been widely used to investigate addictive behaviours, and offers advantages of accessibility, low cost, and excellent temporal resolution. The present systematic review evaluates resting-state EEG studies in GD and IA. Papers ( n  = 7293) were identified in the PsychARTICLES, PsychINFO, Scopus, and Pubmed databases. Following inclusion/exclusion criteria, ten studies remained for evaluation. Results suggest individuals with GD have raised delta and theta activity and reduced beta activity, with coherence analysis suggesting altered brain activity in the mid-to-high frequency range. IA individuals demonstrate raised gamma activity and reduced beta and delta activity. Results suggest that the altered brain activity found in GD/IA may represent distinct underlying neurophysiological markers or traits, lending further support to their unique constructs. Results are also discussed in relation to relevant psychometric measurements and similar (higher frequency) activity found in substance addiction. Future research should focus on replicating the findings in a wider variety of cultural contexts to support the neurophysiological basis of classifying GD and IA.